OC-043 The Role of the EPS8 Binding Partners Sos1 and Abi1 in Pancreatic Cancer. (4th June 2013) - Kiely, P; Tod, J; Jenei, V; Johnson, C; Thomas, G J
Abstract : Introduction: Pancreatic cancer (PC) is an aggressive disease, characterised by marked local invasion, and identification of new molecular targets is critical to improving outcome. Cell motility requires reorganisation of the actin cytoskeleton and several actin-binding proteins have been implicated in PC. EGF receptor pathway substrate 8 (Eps8) is an adapter protein that interacts with a range of intracellular binding partners, including Abi1 and Sos1 (to form a tri-complex), and certain β integrin subunits, in order to regulate cytoskeletal reorganisation. The integrin αvβ6 is overexpressed in approximately 70% of PC and enhances invasion. This study examines the role of the Eps8 binding partners, Abi1 and Sos1, in αvβ6-dependent PC invasion and the significance of their expression on patient survival. Methods: We used immunochemistry to examine the expression of Eps8, Sos1 and Abi1 in normal pancreas and PC in vivo using tissue microarrays. A retrospective patient database of PC patients operated on between 2000 and 2010 was generated. 33 short ( < 1 year) and 20 long ( > 5 years) survivors were then identified and resection tissue stained as whole sections for Eps8/Sos1/Abi1/αvβ6. We identified three PC cell lines that showed αvβ6-dependent invasion in vitro, and examined the role of Abi1 and Sos1 in Transwell® assays to specifically study motility dependent on this integrin. Results: Eps8, Sos1 and Abi1 were up-regulated in PC compared with normal tissue. Expression of these proteins in long and short survivors of PC is currently being examined. Expression of Eps8, Sos1, Abi1 and αvβ6 were confirmed in all three PC cell lines tested. Knock-down of Eps8, Sos1 or Abi1 suppressed αvβ6-dependent invasion suggesting that this tri-complex is critical to PC motility. Conclusion: We have shown that Eps8, Sos1 and Abi1 are up-regulated in PC and regulate αvβ6-dependent function. The Eps8 binding partner Sos1 appears to be critical to αvβ6-dependent PC cell motility. This may be of particular interest as Sos1 expression was previously shown to fall in response to gemcitabine, the current gold standard chemotherapeutic agent for the treatment of PC. Sos1 requires further investigation as a potential molecular target in the treatment of PC. Disclosure of Interest: None Declared